The Last of the Crusaders : The Knights of St. John and Malta in the Eighteenth Century - Cavaliero, Roderick (New York Tauris Parke Paperbacks, 2009)
The Knights Hospitaller of St John and Malta was a militant order of monk-soldiers who alone outlasted the bloody centuries of the Crusades. This book tells the story of the decline of this once mighty order and of the island that was their final sanctuary.
Include Illustrations, Maps, Authorities and Index
Keywords: Knights of Malta -- History -- 18th century -- Malta -- History -- 18th century -- Malta -- History -- 1530-1798